2020
DOI: 10.1177/1463499620958857
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence policies in the Netherlands: A regime of deficiency

Abstract: In a number of countries, domestic violence is represented as a governable phenomenon that is amenable to policy interventions. Over the past 40 years in the Netherlands, however, this approach has not resulted in a reduction of domestic violence. Yet new policy strategies continue to be designed to improve existing interventions. In this article, we focus on a Dutch policy measure that aims to detect early signals of violence and abuse. We argue that this strategy, by approaching domestic violence as a techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…The current study focuses on officially reported incidents of domestic violence in the Netherlands. Domestic violence is used as a generic term for violence perpetrated by someone within the domestic circle of the victims, hence including IPV and child maltreatment, as well as violence against parents and elderly abuse (Mellaard & Meijl, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current study focuses on officially reported incidents of domestic violence in the Netherlands. Domestic violence is used as a generic term for violence perpetrated by someone within the domestic circle of the victims, hence including IPV and child maltreatment, as well as violence against parents and elderly abuse (Mellaard & Meijl, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to poorly defined and under-theorized concepts of empowerment, the choices and resources available to women are increasingly limited. Women seeking help for DV are now often met with similar sets of choices guided by the same general set of values, beliefs, and practices that form the dominant discourse of the GV movement in most western countries (Kasturirangan, 2008;Mehrotra et al, 2016;Mellaard & Meijl., 2021; see also Vaughan et al, 2015, for an Australian context specific to refugees). Centered on gender equality, and often focusing on legal interventions and individualistic notions of breaking up the family (Merry, 2011;Ong, 2003), it is not difficult to see why many women-let alone refugee and migrant women, or even workers supporting themmight find these choices disempowering (Kasturirangan, 2008;Mellaard et al, 2021).…”
Section: Refugees Empowerment and The Human Servicesmentioning
confidence: 99%
“…Earlier feminist activism based on empowerment traversed both the micro and the macro, drawing on collective strategies aimed at both individual and structural change (MacDowell, 2019). Now, however, hierarchical models of service delivery and overly bureaucratic processes limit the decisions women can make (Mellaard & Meijl, 2021). A focus on resourcing for women's shelters and front-line services, the movement's alignment with the rise of therapy culture, public health approaches to risk and surveillance, and the ongoing pursuit of criminalization, have diverted resources away from both material resources and the development of alternative policy and practice responses (Bumiller, 2008;Goodmark, 2018;Mehrotra et al, 2016).…”
Section: Refugees Empowerment and The Human Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…de aard van of het type huiselijk geweld). Bovendien kan huiselijk geweld meerdere vormen aannemen, zoals lichamelijk, seksueel of psychisch geweld (Mellaard & Meijl, 2021;Ten Boom e.a., 2019). Slachtoffers, plegers, omstanders en professionals kunnen bij (vermoedens van) huiselijk geweld contact opnemen met Veilig Thuis, het centrale meld-en adviespunt in Nederland voor huiselijk geweld en kindermishandeling (hierna: huiselijk geweld).…”
Section: Aanleiding En Achtergrondunclassified